THE INFLUENCE OF OPERATIONAL PERFORMANCE ON PROFITABILITY (Survey On Regional Drinking Companies (PDAM) In West Java) - Sjaiful, Rudy Lizwaril; Purnama, Arizka Amalia; Hadiyanto, Dheila Novalinda; Yusuf, Yogi Maulana; Ramadhan, Muhammad Dias (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine the effect of operational performance on profitability at local water companies in West Java Province. The method used in this research is explanatory research method. The population used in this study were all regional drinking water companies in the province of West Java. The sampling technique used was purposive judgment sampling. The analysis used was original least square and processed using the SPSS 21 program. The results showed that the average operational performance achievement of regional drinking water companies in West Java Province reached 1.26. the profitability of PDAMs in West Java is 3.83%, this is very far from the maximum expected target of 10%. The operational performance of regional drinking water companies in West Java has a significant effect on profitability.